Adobe Dreamweaver CS5.5 : designing and developing for mobile with jQuery, HTML5, and CSS3 : studio techniques - Powers, David (Berkeley, Calif. : Adobe Press/Peachpit, 2011)
Provides information on creating websites and applications that work on mobile platforms using Dreamweaver CS5.5.
Includes index.
Keywords: Dreamweaver (Computer file); Dreamweaver (Computer software); Adobe Photoshop (Computer software); Mobile computing; Web sites -- Design; Application software -- Design